Propagation, genetic variation and evaluation of kemunting (Rhodomyrtus tomentosa (aiton) hassk) populations in Malaysia for landscape use - Tan, Siao Hue (2015)
Kemunting (Rhodomyrtus tomentosa) is a multipurpose edible ornamental shrub. Its natural populations are fast diminishing and conservation of the species is urgently needed. No previous study has been conducted in terms of its propagation, genetic variation and evaluation of population for landscape use. A series of experiment were conducted to (i) determine the rooting performance of R. tomentosa populations as affected by different IBA concentrations and types of cutting (ii) document the seed traits and the effects of temperature on germination performance of R. tomentosa from different sources (iii) access the genetic variability among R. tomentosa populations in Malaysia and (iv) evaluate R. tomentosa populations suitable for ornamental landscape. Softwood, semi hardwood and hardwood cuttings from nine natural populations (C01,C02, D01, D02, K01, M01, N01, T01 and T02) were arranged in a three factorial (locations, types of cutting, IBA concentrations) RCBD design with four replications. Subsequently, only softwood cuttings from four natural populations (J01, J02, J03 and Q01), arranged in RCBD with 4 replications were used for rooting assessment. The data obtained were analyzed together with softwood data from the previous nine populations. The cuttings were treated with 0, 800, 1600, 2400 and 3200 mg/L IBA. Histological examination was done to follow the root initiation process. Softwood cuttings gave the best rooting performance regardless of IBA treatments and it should be used in the propagation of R. tomentosa. Cuttings from different populations showed variation in rooting performance, with cuttings from J03 rooted the best (87.3%). Root primordium started to develop from phloem region three weeks after the cuttings were planted. Only seeds from five populations (C02, K03, M01, SA01 and T01) were obtained during the collection and subjected to light, scanning electron microscopy and water imbibition test. Seeds from other populations (C01, D01, D02, J01, J02, J03, K01,K02, N01, Q01, SA02, S01, T02) were obtained from the plants established at Field 2, UPM. Seed morphology from each population was measured. The seeds were germinated at constant (10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C) and fluctuating temperatures (33°C/ 25°C), arranged in CRD with 4 replications. Seeds from all the populations varied in their seed traits and germination performance. Seed structure affect water uptake but not germination. Seeds from all locations except C01, K03 and T01 germinated to a higher percentage in fluctuating temperatures. R. tomentosa seeds germinated slowly and erratically both under constant and fluctuating temperatures. ISSR was utilized to ascertain the genetic variation of 15 R. tomentosa populations. All 18 collections were included in morphological study. Twenty one morphological traits were measured. The 11 primers generated 95.29% polymorphism. Population N01 was the most variable (PPB = 42.35%). The significant population pairwise PhiPT suggested that the populations were isolated. The groupings of populations were according to their geographical origins based on molecular data but not based on morphological characters. ITS analysis showed that it is possible for M01 and N01 to be classified as new variety. The perception of nursery owners, final year students of Bachelor of Horticultural Science (BSHort) and Bachelor of Landscape Architecture (BLA) towards R.tomentosa were assessed using questionnaire with pictorial simulations. R. tomentosa is better known among students (BSHort, 34.8%; BLA, 15.7%) through university (BSHort, 52.9%; BLA, 44.4%). Of the 7.9% of nursery owners, 50% of them know R.tomentosa through friends. Suitablity of R. tomentosa as landscape plant was perceived by 96.6% of the respondents. R. tomentosa is most suitable to be utilized as ornamental hedges (71.9%). The most attractive landscaping features were rounded plant form (56.2%); elliptic leaf shape (60.7%); flower with rounded petals and dense petal arrangement (73%) and rounded fruit with reflexed calyx lobes (42.7%), which was possessed by sample K03 from Langkawi, Kedah except the elliptic leaf shape. In conclusion, R. tomentosa should be propagated using softwood cuttings without IBA or with 1600 mg/L IBA. All the R. tomentosa populations should be conserved in-situ and ex-situ since there is a huge potential for it to be introduced into the Malaysian landscape industry.